Advanced three-dimensional geomechanical and hydrogeological modelling for a deep open pit - Cotesta, L; Xiang, J; Paudel, B; Sterrett, R; Sjöberg, J; Dilov, T; Vasilev, I; Yalamov, Z (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The Ellatzite open pit mine, located in Bulgaria, is a large copper mine with a current mining depth in excess of 500 m. During the last few years, Ellatzite-Med AD and Itasca International Inc. have jointly conducted a large slope stability analysis project utilising an integrated geomechanical and hydrogeological approach with the overall goal of assessing the stability of the open pit slopes for current and future mining. The conducted work has included developing a Geomechanical Framework Model to describe the rock mass in quantitative terms. This model is based on extensive data collection from active open pit walls, boreholes, and drainage tunnels, and includes a detailed interpretation of the lithological and structural characteristics of the site. The structural geology of the site is complex, with a large number of lithological contacts and faults, all interpreted as discontinuities with the potential to slip. Hence, a 3D discontinuum approach was required to represent the geomechanical environment in a numerical model for stability assessment. The approach used enabled including all lithological contacts and faults (more than 50 largescale, undulating, discontinuities) in a mine-scale 3DEC model. A hydrogeological model was developed in parallel to quantify pore pressure conditions in the rock mass. Faults were also included also in the hydro-model, and calculated pore pressures were then exported to the 3DEC model for stability assessment. Joint fabric, simulated as ubiquitous joints, were also included in the geomechanical model. The model results were compared against observations and deformation measurements from the open pit. Near-future mining scenarios were investigated and various mitigating measures, such as drainage and/or slope geometry alterations were developed. The modelling work is at the forefront of what is possible in discontinuum 3D slope stability analysis of complex structural-geological conditions and for practical open pit stability assessments.
Keywords: geomechanical framework model